Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1998
DOI: 10.1115/98-gt-537
|View full text |Cite
|
Sign up to set email alerts
|

Film Thickness, Droplet Size Measurements and Correlations for Large Pressure-Swirl Atomizers

Abstract: A parametric experimental study has been conducted to measure the discharge coefficient, the flow number, the film thickness, the spray angle, the velocity coefficient and droplet size of a large-scale simplex nozzle using ultrasonic and optical techniques. Seventeen nozzle geometries have been studied for three mass flow rates. The large-scale nozzle provides adequate resolution for measurements of film thickness, spray angle, and droplet size. The experimental data collected have been used to derive new and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…He found that the discharge coef cient increases with atomizer constant K , L s / D s , and D s / d o , and decreasesslightly with l o / d o . Recent resultsof Benjamin et al 10 show that these effects are sensitiveto the range of parameter values considered. They have presented correlations for discharge coef cient, lm thickness, and spray angle for large-scale simplex nozzles.…”
mentioning
confidence: 96%
“…He found that the discharge coef cient increases with atomizer constant K , L s / D s , and D s / d o , and decreasesslightly with l o / d o . Recent resultsof Benjamin et al 10 show that these effects are sensitiveto the range of parameter values considered. They have presented correlations for discharge coef cient, lm thickness, and spray angle for large-scale simplex nozzles.…”
mentioning
confidence: 96%
“…They have used the Bloor and Ingham [11] analysis for the boundary-layer flow above a flat disk and they estimated the proportion of the fluid that enters the orifice through the boundary layer. Benjamin et al [12] have investigated the effects of various geometric and flow parameters on the performance of large-scale pressure swirl atomizers using optical methods. In 2001 Hansen et al [13] simulated the Newtonian fluid flow in a scaled model of a pressure-swirl atomizer via commercially available CFX-4.3 code.…”
Section: Figure1: Schematic View Of a Pressure-swirlmentioning
confidence: 99%
“…To validate their code, experiments were conducted on a large scale prototype nozzle using Particle-Image-Velocimetry (PIV) and Laser-DopplerVelocimetry (LDV) methods and high speed digital camera [45]. Detailed comparison of experimental measurements/empirical correlations [46,47,48] and computational results was carried out which showed excellent agreement. The validated computational code was then used to investigate the effects of atomizer geometry under two flow regimes -constant mass flow rate through the atomizer [34,36,45,49] and constant pressure drop across the atomizer [35].…”
Section: Figurementioning
confidence: 99%